LAW AND INEQUALITY: CHILDOOD AND YOUTH AT THE START OF THE 20TH CENTURY - Víquez Jiménez , Paula (2019)
This article analyzes the presence and representation of the child in the decades from 1930 to 1950 in Costa Rica. The work is exploratory and primarily uses laws from the time, records of the Patronato Nacional De la Infancia (National Child Welfare Agency) and newspapers of the time as investigative sources. It follows that the law functioned as an instrument of power which stripped the children from their rights versus adult figures especially those who belonged to the impoverished sectors.